Anhedonia Reduction and the Association Between Left Ventral Striatal Reward Response and 6-Month Improvement in Life Satisfaction Among Young Adults - Eckstrand, Kristen L. (JAMA Psychiatry, 2019)
IMPORTANCE: Anhedonia is a symptom of multiple psychiatric conditions in young adults that is associated with poorer mental health and psychosocial function and abnormal ventral striatum reward processing. Aberrant function of neural reward circuitry is well documented in anhedonia and other psychiatric disorders. Longitudinal studies to identify potential biomarkers associated with a reduction in anhedonia are necessary for the development of novel treatment targets. OBJECTIVE: To identify neural reward-processing factors associated with improved psychiatric symptoms and psychosocial function in a naturalistic, observational context. DESIGN, SETTING, AND PARTICIPANTS: A longitudinal cohort follow-up study was conducted from March 1, 2014, to June 5, 2018, at the University of Pittsburgh Medical Center after baseline functional magnetic resonance imaging in 52 participants between the ages of 18 and 25 years who were experiencing psychological distress. MAIN OUTCOMES AND MEASURES: Participants were evaluated at baseline and 6 months. At baseline, participants underwent functional magnetic resonance imaging during a card-guessing monetary reward task. Participants completed measures of affective symptoms and psychosocial function at each visit. Neural activation during reward prediction error (RPE), a measure of reward learning, was determined using Statistical Parametric Mapping software. Neural reward regions with significant RPE activation were entered as regions associated with future symptoms in multiple linear regression models. RESULTS: A total of 52 young adults (42 women and 10 men; mean [SD] age, 21.4 [2.2] years) completed the study. Greater RPE activation in the left ventral striatum was associated with a decrease in anhedonia symptoms during a 6-month period (β = −6.152; 95% CI, –11.870 to –0.433; P = .04). The decrease in anhedonia between baseline and 6 months mediated the association between left ventral striatum activation to RPE and improvement in life satisfaction between baseline and 6 months (total [c path] association: β = 0.245; P = .01; direct [c′ path] association: β = 0.133; P = .16; and indirect [ab path] association: 95% CI, 0.026-0.262). Results were not associated with psychotropic medication use. CONCLUSIONS AND RELEVANCE: Greater left ventral striatum responsiveness to RPE may serve as a biomarker or potential target for novel treatments to improve the severity of anhedonia, overall mental health, and psychosocial function.